2020
DOI: 10.1080/10691898.2020.1834475
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped Classroom in Introductory Statistics: Early Evidence From a Systematic Review and Meta-Analysis

Abstract: The flipped classroom (FC) inverts the traditional classroom by having students participate in passive aspects of learning at home and active aspects of learning in class with the guide of an instructor. The introductory statistics course for non-math majors may be especially suited to the FC model given its unique challenges as a required course for students with varying mathematical skills and background. For example, these students often have low interest and high statistics related anxiety. Recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…The self-paced learning at home and the learning activities in classes can also result in higher levels of satisfaction [55] and engagement [56]. Based on a metaanalysis [48] it is highlighted that student's performance was higher in a flipped classroom than in a traditional classroom in most of the examined studies. The paper of Gundlach et al (2015) showed that traditional students scored higher on average on the exams compared to flipped students but Gundlach et al explain that by less face-to-face class time in the flipped classroom compared to the traditional one or by the instructor's higher experience on the traditional lecture [57].…”
Section: Flipped Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…The self-paced learning at home and the learning activities in classes can also result in higher levels of satisfaction [55] and engagement [56]. Based on a metaanalysis [48] it is highlighted that student's performance was higher in a flipped classroom than in a traditional classroom in most of the examined studies. The paper of Gundlach et al (2015) showed that traditional students scored higher on average on the exams compared to flipped students but Gundlach et al explain that by less face-to-face class time in the flipped classroom compared to the traditional one or by the instructor's higher experience on the traditional lecture [57].…”
Section: Flipped Classroommentioning
confidence: 99%
“…problemsolving, assignments, group work, quizzes, etc.) with a peer mentor and instructor support available" [48]. This approach has emerged from primary and secondary education [49] and became popular in post-secondary education about a decade ago [50].…”
Section: Flipped Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this philosophy has been incorporated in the introductory courses. In recent years there has been a wealth of literature on innovations in introductory statistics and data science courses (e.g, Adams et al 2021, C ¸etinkaya-Rundel & Ellison 2021, Farmus et al 2020, Baumer 2015, Hardin et al 2015. Many of these innovations, have been motivated by the need to help students gain the conceptual knowledge and computing skills required to analyze authentic complex and nonstandard data, such as analyzing text and spatial data.…”
Section: Curriculum Guidelines and Related Workmentioning
confidence: 99%
“…Flipped classroom adalah satu kaedah pedagogi yang biasa digunakan bagi peringkat pengajian tinggi selepas sistem persekolahan. Ia adalah satu kaedah yang berpandukan model blended learning yang menukar paradigma kaedah pengajaran tradisional dari segi tugasan dan pendekatan pengajaran di dalam kelas (Farmus et al, 2020). Idea di sebalik kaedah ini memerlukan maklumat dan panduan pengajaran dijalankan di luar masa kelas.…”
Section: Pengenalanunclassified